Laparoscopic Versus Open Total Gastrectomy for Advanced Gastric Cancer: A Multicenter, Propensity Score-Matched Cohort Study in China - Feng, Xingyu; Chen, Xin; Ye, Zaisheng; Xiong, Wenjun; Yao, Xueqing; Wang, Wei; Wang, Junjiang; Chen, Luchuan; Li, Yong (Frontiers in Oncology, 2021)
Background: Given the great technical difficulty and procedural complexity of laparoscopic total gastrectomy (LTG), the technical and oncologic safety of LTG versus open total gastrectomy (OTG) in the field of advanced gastric cancer (AGC) is yet undetermined. Objective: This multicenter cohort study aimed to compare the surgical and oncological outcomes of LTG with those of OTG in AGC patients. Patients and Methods: In total, 588 patients from 3 centers who underwent primary total gastrectomy with D2 lymphadenectomy, by well-trained surgeons with adequate experience, for pathologically confirmed locally AGC (T2N0-3, T3N0-3 or T4N0-3) between January 1, 2011, and December 31, 2015, were identified, and their clinical data were collected from three participating centers. After 1:1 propensity score matching (PSM), 450 cases (LTG, n=225; OTG, n=225) were eligible and assessed. Results: No significant difference in the number of retrieved lymph nodes, 5-year disease-free survival (DFS) rates, and 5-year overall survival (OS) rates between both surgical groups were observed. Although LTG had significantly longer surgical time (262 vs. 180 min, P < 0.001), LTG was associated with fewer postoperative complications [Relative risk (RR) 0.583, 95% CI 0.353-0.960, P = 0.047), less intraoperative bleeding (120 vs. 200 mL, P < 0.001), longer proximal margin resection (3 vs. 2 cm, P < 0.001), and shorter postoperative hospitalization (11 vs. 13 days, P < 0.001). The mortality rate was comparable in both groups. Conclusions: LTG was not inferior to OTG in terms of survival outcomes, was associated with shorter surgical and postoperative hospitalization time and fewer postoperative complications; suggesting LTG with D2 lymphadenectomy as an important alternative to OTG for patients with AGC, but to be carried out in high experience centers.